Minority Marketing: Research Perspectives for the 1990s: Proceedings of the 1993 Minority Marketing Congress - King, Robert L (Springer, 2015)
This volume includes the full proceedings from the 1993 Minority Marketing Congress held in Long Beach, Mississippi under the theme Minority Marketing: Research Perspectives for the 1990s. It provides a variety of quality research in the field of minority marketing in order to assimilate and enhance knowledge of marketing practices for minority enterprises. It includes papers on various topics in minority marketing including advertising, promotion and consumer behavior.